An evidence-based scoring system for prioritizing mosaic aneuploid embryos following preimplantation genetic screening. Issue 4 (April 2018) - Grati, Francesca Romana; Gallazzi, Gloria; Branca, Lara; Maggi, Federico; Simoni, Giuseppe; Yaron, Yuval
Abstract: The aim of this study was to devise an evidence-based scoring system for prioritizing mosaic aneuploid embryos for transfer. A retrospective analysis was performed of all sequential cytogenetic and molecular results on chorionic villi samples ( n = 72, 472) and products of conception ( n = 3806) analysed at a single centre. The likelihood that a mosaic aneuploidy detected in chorionic villi samples will involve the fetus, the incidence of clinically significant fetal uniparental disomy in the presence of a mosaic in chorionic villi and the chance of the mosaicism culminating in miscarriage were used to generate a scoring system for prioritizing mosaic aneuploid embryos detected by preimplantation genetic screening. A composite score was obtained for each individual mosaic aneuploidy after assignment of an individual risk score based on the incidence/likelihood of each adverse outcome. A final additional score was assigned to viable full or mosaic aneuploidies with a well-defined phenotype. The higher the composite score the lower the priority for embryo transfer. In conclusion, due to the paucity of prospective studies on the actual transfer of mosaic aneuploid embryos, we suggest using this evidence-based scoring system to provide a useful tool for clinicians, embryologists and patients.